Avaliação da presença de Toxoplasma gondii em quibes crus e em carnes suína e bovina comercializadas em Botucatu-SP - Generoso, Diego [UNESP] (2013)
Toxoplasma gondii is an obligate intracellular protozoan parasite, widely distributed throughout the world, accounting for losses in animal production and serious public health problem. The meat products may harbor infectious forms of various zoonotic agents, one of them being the bradyzoites of T. gondii. Thus, the present study aimed to determine the prevalence of T. gondii in meat products marketed in Botucatu, SP, Brazil. We analyzed 141 commercial cuts of pork (ham, 49; 34.75%) and beef (muscle, 48, 34.04%), and raw kibbe (44, 31.21%) by bioassay in mice, and survey of parasite DNA by polymerase chain reaction (PCR) gene repetitive 200- 300x in the genome, amplifying 529bp. All samples were negative by bioassay. Of the PCR-positive samples were studied parasite load by quantitative PCR (qPCR) of the same gene, using the SYBR Green system and the multiplex genotyping, nested PCR and RFLP markers using 11: SAG1, 5'-3 ' SAG2, alt.SAG2, SAG3, B-TUB, GRA6, L358, c22-8, c29-6 PK1, Apico. Of the samples studied, nine (6.38%) were positive for PCR, five (55.56%) for cattle, three for pork (33.33%) and one for raw kibbe (11.11%), with median parasite load ranging from 16 to 390 parasitos.mL-1. Genotyping was possible in only one sample that showed genotype similar to those already identified in the literature (MAS, TgCkBr89 and TgCkBr147). In addition, nested PCR and RFLP gene 18S ribosomal RNA (18S rRNA) sequencing of the nested-PCR products and alignment to the GenBank database at NCBI were performed for all nine positive samples to verify the possibility of co-protozoa infection with other Apicomplexa, resulting in 100% homology with T. gondii in four samples, three from pork meat sows and one from kibbe (44.44%; GenBank accession number L37415.1), Sarcocystis hominis was foundin two samples of cattle (22.22%, GenBank accession number AF006471.1), Sarcocystis cruzi in two samples of beef (22.22%; GenBank ...